THE EFFECT OF CREDIT AND CAPITAL ON INCOME OF MEMBERS OF DUMI DIGITAL TECHNOLOGY SAVE AND LOAN COOPERATIVES IN BANDUNG CITY - Muhiban, Ayi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research was conducted on members of the Dumi Digital Technology Savings and Loan Cooperative in Bandung. The purpose of this study was to determine how big the contribution of the influence of credit and capital to income either partially or simultaneously on the members of the Dumi Digital Technology Savings and Loans Cooperative in Bandung City. The research method that will be used in this research is descriptive and associative methods. In this study, the unit of analysis is the individual, namely the member of the Dumi Digital Technology Savings and Loan Cooperative in Bandung City. The sample in this study were 134 respondents. Sampling using Simple Random Sampling is a sampling technique used in this study. The method of analysis used multiple linear regression analysis, in addition to testing the validity and reliability of the research instrument. Based on the results of the study, it shows that there is an effect either partially or simultaneously on exogenous variables (credit and capital) on endogenous variables (income). The implication of this research is that the Dumi Digital Technology Savings and Loan Cooperative in Bandung City can perform a more optimal analysis of the assessment of prospective debtors, evaluate the requirements given to prospective debtors so that these requirements do not become an obstacle factor for members in receiving additional capital.